Analysis of Netizen Responses to News Violations Of Religious Norms on Oklin Fia Ice Cream Lick Content: Analisis Respon Netizen Terhadap Berita Pelanggaran Norma Agama Pada Konten Jilat Es krim (Indonesian Journal of Cultural and Community Development, 2024)
General Background: Instagram has emerged as a significant platform for communication, enabling the dissemination of programs and policies while provoking a range of opinions, discussions, and perceptions among users. Specific Background: This study examines the responses generated by netizens to news content shared on the Instagram account @liputan6, focusing on the nature of their comments in relation to the conveyed messages. Knowledge Gap: While existing literature has explored social media interactions, there is limited research specifically addressing the types of responses elicited by news content on Instagram and how these responses align with established communication theories. Aims: The study aims to analyze netizen responses using the Stimulus-Organism-Response (S-O-R) theory to categorize comments into cognitive, affective, and conative responses. Results: Findings reveal that netizen responses predominantly manifest as cognitive and affective reactions, with a minimal presence of conative responses. The results indicate that inconsistencies between the news content and netizens' pre-existing knowledge and feelings lead to a higher incidence of cognitive and affective comments. Novelty: This research contributes to the understanding of user engagement on social media by elucidating the types of responses elicited by news content.Highlights: • Diverse Responses: Netizen comments primarily exhibit cognitive and affective responses rather than conative reactions.• Knowledge Inconsistency: Inconsistencies between news content and netizens' pre-existing knowledge contribute to the prevalence of cognitive and affective reactions.• Engagement Strategies: Understanding response types can enhance strategies for effective engagement and content delivery on social media platforms.Keywords: Instagram, Netizen Responses, S-O-R Theory, Cognitive, Affective